Arabic Language For Global Entrepreneurship: Empowering Islamic Studies Students For Beginner Level With An Innovative Vocabulary Board Game I-Mufradaat - Nor Zahidah Ahmad; Najihah Abd Wahid; Fitri Nurul'ain Nordin; Nursafira Ahmad Safian; Lily Hanefarezan Asbulah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
I-Mufradaat is a language board game specifically designed and developed for learning Arabic vocabulary at the tertiary level, adapting the psychological basis of Howard Gardner's Multiple Intelligences Theory alongside Bloom’s Taxonomy (Krathwohl & Anderson, 2009). This product primarily focuses on improving Arabic vocabulary and describes the steps for developing an Arabic Board game product to enhance Arabic vocabulary acquisition among Islamic Studies students at the beginner level at Universiti Sultan Zainal Abidin (UniSZA). The type of research is Design and Development research with the ADDIE development model, which is modified into five steps of development, namely 1) Need analysis of the product. (2) Design content. (2) Development of initial product draft. (4) Implementation of the end-product. (5) Evaluation. The instruments used were expert validation questionnaires. The respondents in this research are 234 students from the Faculty of Islamic Contemporary Studies at the University Sultan Zainal Abidin (UniSZA), Terengganu. This research uses a questionnaire as a way of collecting data and the SPSS statistical package to analyze the data. The expected results are that there is a need for the development of an Arabic Board game, which is very appropriate as an innovative platform to be used in learning Arabic vocabulary. The features of Arabic Board game emphasize steps for making a game consisting of a game board, card, game manual and game assessment sheet.